The Use of Web Applications in improving English Skills of Non-native English Speakers in UHW Perbanas Surabaya - Budiana, Kartika Marta; Yutanto, Hariadi; Ilham, Romi; Rokhmania, Nur`aini (Universitas Negeri Semarang, 2023)
More innovation in teaching English to students is required due to the importance of English itself. Language teachers cannot be far from technology in this process, which is the application of scientific knowledge to practical tasks by organizations involving both people and machines. This study intends to see use of the Web applied on students` English skill. This study adopt a mixed-method approach. The method is chosen to elaborate the data taken from the students who apply Web on their study at UHW Perbanas Surabaya. There are several instruments used here to collect the data relate to the teaching method applied. The research instruments in this study is a questionnaire. The students` experience suggested that (1) the web application aids their English learning (2) the students agreed that utilizing the Kulon program enables them to complete English grammatical exercises more quickly (3) the web application enabled them to get higher scores on ESP subjects rather than English courses in the previous semester